Economic Analysis of the Losses of Oil Palm (Elaeis guineensis Jacq.) Loose Fruits on Flat Terrain at Agritasari Prima Ltd. - Rannando; Tujannah, Mawaddah; Azmi, Yudia; Sahfitra, Angga Ade (Open Science and Technology, 2025)
Aims and Methods: Oil palm is a strategic commodity that contributes significantly to Indonesia's economy. The losses of oil palm loose fruits during the harvesting and transportation processes of fresh fruit bunches (FFB) pose a serious challenge for oil palm plantation industry, with potential losses reaching 3–7% of total production. This study aims to analyze the distribution pattern of the losses of loose fruits at three observation points (weed circle, carrying market, and harvest collection point (HCP)) at Agritasari Prima Ltd., calculate the economic loss due to these losses, and identify the causative factors. This study employs a qualitative descriptive survey method with sampling at three plantation divisions on flat terrain, covering 1,260 weed circles, 21 carrying markets, and 144 HCPs.Results: The highest loss distribution occurred at carrying market (47.66 fruits/carrying market), followed with weed circle (10.15 fruits/circle) and HCP (8.14 fruits/site). The total economic loss reached IDR 463,143.83, with the largest contribution coming from the losses at weed circle of 85.44% (IDR 395,808), followed by HCP of 7.86% (IDR 36,307), and carrying market of 6.70% (IDR 31,028.83). The annual economic loss due to the losses of loose fruits on flat terrain at Agritasari Prima Ltd. is estimated at IDR 2,178,282,597.31 (around IDR 2.18 billion per year). Major causative factors comprise poorly maintained weed circles, overloaded wheelbarrows, poor route infrastructure at carrying markets, and suboptimal handling at HCPs.Conclusion: Implementation of regular maintenance programs, standardization of vehicles’ capacity, infrastructure improvements, and digital monitoring systems are recommended to reduce the level of losses of loose fruits and improve oil palm plantation operational efficiency.